Volatile-char interactions: Roles of in situ volatiles with distinctly-different chemistry in determining char structure and reactivity - Chen, X.; Wu, Hongwei (Combustion Institute, 2018)
© 2018 The Combustion Institute. This study reports the roles of volatiles with distinctly-different chemistry in determining char reactivity and char structure during in situ volatile-char interactions under non-catalytic conditions. Volatiles were generated in situ from polyethylene (PE), double-acid washed biosolid (DAWB), polyethylene glycol (PEG) or cellulose and interacted with char prepared from DAWB that is free of catalytically-active inorganic species in a two-stage reactor at 1000 °C. The experimental results show that both H- and O-containing reactive species play different roles during in situ volatile-char interactions. It has been found that char reactivity decreases substantially after in situ volatile-char interactions. Results from Raman analysis of the char after in situ interactions with the PE volatiles show H-containing reactive species substantially enhance the condensation of the aromatic ring systems within the char, thus slightly decreasing the H content in char and also making char carbon structure considerably less reactive. It has also been found that the reactivity of char after in situ volatile-char interactions increases with increasing O/H molar ratio of volatiles. The results indicate that O-containing reactive species in volatiles can react with char to form C. O complex oxides that mitigate the carbon structure from condensing into large aromatic ring systems, thus increasing O and H contents in char and enhancing char reactivity.